Why do business angels invest? Uncovering angels’ goals - Rui Falcão; Maria João Carneiro; António Carrizo Moreira (Cogent Business & Management, 2023)
AbstractDespite the increasing importance of business angels (BAs) as crucial players in the growth of high-potential early-stage startups, their motivations are not fully understood. Many of the perceptions of BAs deviate significantly from more conventional views of conventional economic and financial models. To gain a comprehensive understanding of BAs’ goals, qualitative techniques from marketing and consumer behaviour as additional lenses (including laddering and means-ends chains) were employed to allow currently active BAs to articulate their goals in ways that forced-choice, quantitative methods do not achieve. Additionally, to determine if entrepreneurs perceive BAs in the same way BAs see themselves, entrepreneurs were asked to provide their perspectives on why BAs choose to become angel investors, based on their experiences with BAs. The findings reveal that traditional financial viewpoints do not adequately capture the depth and driving force behind BAs’ goals, while entrepreneurs appear to be overly influenced by conventional assumptions about these goals. The study also provides valuable insights into the relationships and hierarchy among BAs’ goals, and on the relevance of each goal. The paper ends with reflections on the practical implications of this research for BAs, entrepreneurs and policymakers.